2021
DOI: 10.1021/acsmedchemlett.1c00591
|View full text |Cite
|
Sign up to set email alerts
|

Design of Coibamide A Mimetics with Improved Cellular Bioactivity

Abstract: Coibamide A, a cyclic depsipeptide isolated from a Panamanian marine cyanobacterium, shows potent cytotoxic activity via the inhibition of the Sec61 translocon. We designed a coibamide A mimetic in which the ester linkage between MeThr and d -MeAla in coibamide A was replaced with an alkyl linker to provide a stable macrocyclic scaffold possessing a MeLys(Me) residue. Taking advantage of a facile solid-phase synthetic approach, an structure–activity relationship (SAR) study of the newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…112 Total syntheses of bastimolides A and B, 113,114 and the 10-aza-9oxakalkitoxin analogue of kalkitoxin 115 were reported in 2022. Other notable work on cyanobacterial NPs included a report on the biosynthesis of the carbon skeleton of nocuolin, 116 synthesis of coibamide A mimetics with improved cellular bioactivity, 117 and an evaluation of antitrypanosomal activity of gallinamide and analogues. As has been the case in previous years, the genus Aspergillus was overwhelmingly the most common source of fungal metabolites this year.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…112 Total syntheses of bastimolides A and B, 113,114 and the 10-aza-9oxakalkitoxin analogue of kalkitoxin 115 were reported in 2022. Other notable work on cyanobacterial NPs included a report on the biosynthesis of the carbon skeleton of nocuolin, 116 synthesis of coibamide A mimetics with improved cellular bioactivity, 117 and an evaluation of antitrypanosomal activity of gallinamide and analogues. As has been the case in previous years, the genus Aspergillus was overwhelmingly the most common source of fungal metabolites this year.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…20 We also previously investigated modification of the CbA macrolactone substructure. 21 CbA mimetic 2a, in which the D-MeAla 11 -MeThr 5 moiety at the ring junction was substituted with a simple MeLys(Me) (Figure 1B), displayed moderate cytotoxic activity. 21 This lysine-linked CbA mimetic was applicable to our lead optimization campaign, in which we revealed that substitution of Tyr(Me) 10 in CbA with (biphenylyl)alanine (Bph) led to a significant increase in cytotoxic potential.…”
mentioning
confidence: 99%
“…Yao et al reported an SAR study which demonstrated that the potent cytotoxic activity of CbA was maintained when the two N , O -dimethylserines [MeSer­(Me)] in CbA were replaced with N -methylalanines (MeAla), whereas most derivatives with simplified structures were less potent (Figure A) . We also previously investigated modification of the CbA macrolactone substructure . CbA mimetic 2a , in which the d -MeAla 11 -MeThr 5 moiety at the ring junction was substituted with a simple MeLys­(Me) (Figure B), displayed moderate cytotoxic activity .…”
mentioning
confidence: 99%
See 2 more Smart Citations